Factors determining pro-ecological behaviour and attitudes of clients of co-operative banks in Malopolskie Province - Szafrańska, Monika (Czynniki determinujące proekologiczne zachowania i postawy klientów banków spółdzielczych w województwie małopolskim, 2020)
The main goal of this paper is to provide the description of pro-ecological behaviour and attitudes of clients of cooperative banks as well as to identify selected factors determining those. The main source of data for analysis and conclusions was provided by primary information. The research tool took the form of a survey questionnaire. The purposive sampling was used (310 respondents). Statistical analysis included total statistical indicators and the logistic regression model. Based on the performed studies, it can be stated that in the consumers’ opinion banks established on cooperative principles engage in matters related to environmental protection more than commercial banks. Gender and average monthly per capita income within the consumer’s household were the factors determining the pro-ecological behaviour and attitudes of clients of cooperative banks
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 3, s. 175-186
Keywords: determinants; cooperative bank; eco-consumption; bank's client; environmental responsibility; determinanty; bank spółdzielczy; ekokonsumpcja; klient banku; odpowiedzialność za środowisko